ENSURING RELIABILITY AND PERFORMANCE LIGHTING SYSTEMS CIVIL AERODROMES - Ільєнко, С.С. (Science-based technologies, 2013)
One of the main tasks is to ensure civil aviation security and regularity of aircraft operations. In reduced visibility airport lighting system (ALS) for the crew is the sole source of information on the stage of visual flying. According to this, the reliability of the ALS must conform to the required regulatory and technical documents level. Reliability - the property of the ALS, which reflects its ability to perform its required function for a specified period of time under specified conditions the operation, maintenance, storage and transportation, and includes reliability, durability, maintainability, and persistence, or a combination of these properties. The task of the study are reliability and maintainability of the ALS and the lighting characteristics lighting equipment ALS subsystems.